2019
DOI: 10.3390/microorganisms7070199
|View full text |Cite
|
Sign up to set email alerts
|

The Host-Microbe Interplay in Human Papillomavirus-Induced Carcinogenesis

Abstract: Every year nearly half a million new cases of cervix cancer are diagnosed worldwide, making this malignancy the fourth commonest cancer in women. In 2018, more than 270,000 women died of cervix cancer globally with 85% of them being from developing countries. The majority of these cancers are caused by the infection with carcinogenic strains of human papillomavirus (HPV), which is also causally implicated in the development of other malignancies, including cancer of the anus, penis cancer and head and neck can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
90
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(96 citation statements)
references
References 135 publications
(151 reference statements)
1
90
0
Order By: Relevance
“…Clinical and epidemiological evidence supports the contribution of various viruses, including EBV, hepatitis virus, cytomegalovirus with gastritis and gastric cancer induced by H. pylori [67], and several studies have shown that gastric microbiota can regulate H. pylori infection and vice versa; this bacterium can modify the gastric microbiota composition [68][69][70]. On the other hand, the microbiota composition in several body niches exerts direct or indirect effects on virus infections, including EBV and human papilloma virus [71]. Therefore, testing potential crosstalk between EBV and H. pylori with gastric microbiota is an interesting line of investigation for further studies.…”
Section: Discussionmentioning
confidence: 97%
“…Clinical and epidemiological evidence supports the contribution of various viruses, including EBV, hepatitis virus, cytomegalovirus with gastritis and gastric cancer induced by H. pylori [67], and several studies have shown that gastric microbiota can regulate H. pylori infection and vice versa; this bacterium can modify the gastric microbiota composition [68][69][70]. On the other hand, the microbiota composition in several body niches exerts direct or indirect effects on virus infections, including EBV and human papilloma virus [71]. Therefore, testing potential crosstalk between EBV and H. pylori with gastric microbiota is an interesting line of investigation for further studies.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, toll-like receptors (TLRs) act as a first-line of defense in recognizing viral infection and foreign bacteria. TLR9 has been suggested to recognize HPV infections and initiate an immune response, while E6 and E7 oncoproteins directly down-regulate TLR9 at a transcriptional level [19]. BV incidence has been associated with SNPs in TLR2/7, but their exact roles in BV are not well understood [20].…”
Section: Microbiome Factors In Cervical Intraepithelial Neoplasiamentioning
confidence: 99%
“…Human papillomaviruses (HPVs) represent a subset of papillomaviruses that are known to infect human hosts and to contribute toward carcinogenesis as etiologic drivers in a wide variety of cancers [1]. Virtually all cervical cancers are associated with high-risk human papillomavirus infections [1,2]. In addition, the landscape of HPV-related neoplasia continues to expand, including a spectrum of head and neck, anal, vulvar, penile, and vaginal carcinomas [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The risk for persistence of HPV infection appears to be influenced by both biological and environmental factors, including age, ability to mount an immune response, hormonal status, dietary habits, tobacco and alcohol usage, and coinfection with other sexually transmissible agents [5]. The specific HPV type involved in infection is also critical for prognosis because HPVs are highly tissue-tropic, with some high-risk types linked to persistent infection and induction of carcinogenesis [2][3][4].…”
Section: Introductionmentioning
confidence: 99%